Acquired Muscle Weakness in the Surgical Intensive Care Unit: Nosology, Epidemiology, Diagnosis, and Prevention. (January 2016) - Farhan, Hassan; Moreno-Duarte, Ingrid; Latronico, Nicola; Zafonte, Ross; Eikermann, Matthias
Abstract : Muscle weakness is common in the surgical intensive care unit (ICU). Low muscle mass at ICU admission is a significant predictor of adverse outcomes. The consequences of ICU-acquired muscle weakness depend on the underlying mechanism. Temporary drug-induced weakness when properly managed may not affect outcome. Severe perioperative acquired weakness that is associated with adverse outcomes (prolonged mechanical ventilation, increases in ICU length of stay, and mortality) occurs with persistent (time frame: days) activation of protein degradation pathways, decreases in the drive to the skeletal muscle, and impaired muscular homeostasis. ICU-acquired muscle weakness can be prevented by early treatment of the underlying disease, goal-directed therapy, restrictive use of immobilizing medications, optimal nutrition, activating ventilatory modes, early rehabilitation, and preventive drug therapy. In this article, the authors review the nosology, epidemiology, diagnosis, and prevention of ICU-acquired weakness in surgical ICU patients. Abstract : Muscle weakness is a common complication in the surgical intensive care unit. This complication is preventable. Early identification with the appropriate diagnostic methods and employment of preventative strategies can improve perioperative patient outcomes.